Generational Analysis of Financial Decision- Making Among Gen-X, Gen-Y, and Gen-Z - Sudaryo, Yoyo; Suryaningprang, Andre; Sumawidjaja, Riyandi Nur; Febriyanti, Diah; Zulfiqar, Mochammad (Operations Research: International Conference Series, 2025)
This study aims to examine the influence of demographic factors on the financial decision-making behavior of three generational cohorts Gen-X, Gen-Y, and Gen-Z in urban Indonesia, focusing on Jakarta, Bandung, and Surabaya. Using a quantitative approach, data were collected through an online survey with 381 respondents and analyzed using ANCOVA and Kruskal- Wallis tests. The findings reveal that income significantly impacts financial decision-making, with higher-income individuals making more informed choices. Women and Gen-Y demonstrate stronger saving discipline and cost-optimization strategies, while city- specific patterns highlight differences in financial behaviors, such as timely payments and discount awareness. Gender and occupation show no significant overall effects, though some variations exist in specific behaviors. These results provide theoretical insights into behavioral accounting, particularly in understanding the role of income and demographic contexts in shaping financial behaviors. Practically, the study informs financial advisors and policymakers to design tailored education and advisory programs for different demographic groups. The study offers a novel contribution by utilizing ribbon chart visualizations to uncover intergenerational and intercity financial behavior patterns in Indonesia.